The role of capital intensity in mediating CEO risk-taking, sustainability reporting, aggressive tax strategies, and financial reporting - Mujennah; Narsa, I Made (International Journal of Management and Sustainability, 2024)
This study explores the influence of CEO risk-taking, sustainability reporting, and aggressive tax practices on financial reporting quality, focusing on the mediating role of capital intensity. Data from 2,305 companies listed in Indonesia over five years were analyzed using path analysis, with the Baron and Kenny approach employed to identify significant mediation effects. The findings reveal that CEO risk-taking, sustainability reporting, and aggressive tax practices indirectly impact financial reporting quality through capital intensity. The study also underscores the role of materiality gaps in sustainability reporting and tax non-compliance in shaping financial reporting outcomes. Capital intensity emerges as a crucial mediator, linking these factors to financial reporting quality. The results suggest that these indirect effects are significant and should be considered in corporate governance and financial management. To improve financial reporting quality, companies must recognize the role of capital intensity, while regulators and policymakers should address sustainability reporting standards and the discrepancies between accounting and tax regulations.